2018
DOI: 10.1038/s41419-018-0821-5
|View full text |Cite
|
Sign up to set email alerts
|

A lincRNA-p21/miR-181 family feedback loop regulates microglial activation during systemic LPS- and MPTP- induced neuroinflammation

Abstract: The role of microglial-mediated sustained neuroinflammation in the onset and progression of Parkinson’s disease (PD) is well established, but the mechanisms contributing to microglial activation remain unclear. LincRNA-p21, a well studied long intergenic noncoding RNA (lincRNA), plays pivotal roles in diverse biological processes and diseases. Its role in microglial activation and inflammation-induced neurotoxicity, however, has not yet been fully elucidated. Here, we report that lincRNA-p21 promotes microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 58 publications
1
55
0
1
Order By: Relevance
“…Purified RNA of 300 ng was used for reverse transcription, qPCR was performed to evaluate the RNA levels. 29…”
Section: A Merip-qpcr Assaymentioning
confidence: 99%
“…Purified RNA of 300 ng was used for reverse transcription, qPCR was performed to evaluate the RNA levels. 29…”
Section: A Merip-qpcr Assaymentioning
confidence: 99%
“…For example, studies in postmortem and 1-methyl-4phenyl-1,2, 3, 6-tetrahydropyridine (MPTP)-induced animal models of PD have shown that microglia are evidently activated in the substantia nigra of the midbrain (7). Alterations in the CNS environment, such as the impairment or death of DA neurons, can directly result in microglial activation, which leads to increased levels of reactive oxygen species (ROS) and proinflammatory cytokines, causing apoptosis and DA cell death (8)(9)(10). Moreover, the pathologic process aggravates the primary morbid process.…”
mentioning
confidence: 99%
“…Briefly, BV2 cells were collected and lysed with the buffer provided in the kit, and the anti-EZH2 antibody or control IgG (negative control) was used to perform the immunoprecipitation. After purification with RNAiso Plus (Takara, Japan), RT-qPCR analysis was performed to evaluate the RNA levels [ 28 ]. RIP enrichment represented the fold change of lncRNA immunoprecipitated by the antibody against EZH2 compared to that immunoprecipitated by IgG.…”
Section: Methodsmentioning
confidence: 99%